Gambang Semarang in the Context of Coastal Culture: Revitalizing Local Wisdom for Education and Tourism - Raharjo, Eko Raharjo; Herdiati, Dian Herdiati; Arsih, Utami Arsih; Lanjari, Restu Lanjari; Hutagalung, Fonny Dameaty (Resital: Jurnal Seni Pertunjukan, 2024)
This research discusses the revitalization of Gambang Semarang in the context of coastal culture as a strategy to preserve traditional arts through education and tourism approaches. As one of Semarang's distinctive art forms, Gambang Semarang reflects cultural acculturation and has excellent potential to be developed in art education and cultural tourism promotion. This research explores strategies for integrating Gambang Semarang into the education curriculum and its development as a cultural-based tourist attraction. The research used a qualitative approach with a case study method involving interviews with stakeholders, observations, and documentation studies in Semarang schools, arts communities, and tourist destinations. The results showed that experiential arts learning and arts community engagement contributed significantly to increasing students' appreciation of Gambang Semarang. In addition, cultural festivals and arts-based tourism programs are effective strategies for expanding Gambang Semarang's exposure to the public and tourists. However, challenges in regenerating young artists and limited promotion remain significant obstacles. The impact of this research shows that the synergy between education and tourism can be an innovative solution for the preservation of Semarang Gambang while contributing to the strengthening of the cultural identity of Semarang's coastal communities and increasing the attractiveness of local cultural tourism.